Десять игр с временем. Концептуализация времени в поэзии Инны Лиснянской - Nikadem-Malinowska, Ewa (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Inna Lisnianska, a Russian poet born in 1928, debuted in the late 1950s and has been publishing intellectual and inspired poetry since then. One of her major artistic achievements has been the creation of the linguistic concept of time. The poems that were selected for this analysis show the poet’s ability to recognize the signs of time “in everything” (M. Bachtin).
Ten plays with time. The conceptualization of time in the poetry of Inna Lisnianskaya
Dziesięć zabaw z czasem. Konceptualizacja czasu w poezji Inny Lesnianskiej